Strategi Upaya Pencegahan Defisit Perawatan Diri Pada ODGJ Di Pasar Minggu Kelurahan Belakang Pondok Kecamatan Ratu Samban Kota Bengkulu - Rina Novita; Dira Bernika Ayu; Tensi Lestari; Siti Sarah; Lhegya Tin Jannah; Della Sutri Juwita; Ade Herman Surya Direja (Lembaga Pengembangan Kinerja Dosen, 2024)
Mental health disorders are health disorders that cause psychological behavioral disorders due to disturbances in social, psychological, hereditary, physical, chemical and biological functions. Self-care deficit is a condition where sufferers experience problems with their ability to carry out or complete self-care activities such as bathing, dressing, eating and toileting. The aim of this community service is to provide effective implementation of SPTK in improving self-care and quality of life for ODGJ. The method used is the implementation of SPTK for ODGJ with self-care deficits. This activity was carried out at Pasar Minggu, Behind Pondok sub-district, Ratu Samban sub-district, Bengkulu City. Meanwhile, this research was carried out on Monday 30 October 2023. After carrying out this activity, ODGJ can find out how to care for personal hygiene and nail care and know how to do it independently. The conclusion of this activity is that strategies for preventing self-care deficits in people with homeless mental disorders need to be developed and implemented holistically by involving various related parties.